CULTURAL TRADITIONS IN DEATH RITUALS WITHIN THE COMMUNITY OF PIDIE, ACEH, INDONESIA - Abdul Manan; Muhammad Arifin (State Islamic University North Sumatra, 2019)
Abstrak: Tradisi Kultural Kenduri Kematian dalam Masyarakat Pidie Aceh, Indonesia. Penelitian ini dilakukan untuk melihat akulturasi budaya dan agama dalam ritual kematian di Aceh. Penelitian ini bertujuan untuk menguji konsep tasawuf yang terkait dengan tradisi ini. Penelitian ini adalah penelitian lapangan dan datanya diperoleh melalui pengamatan yang cermat dari tindakan ritual dan diskusi mendalam dengan protagonis utama dari kinerja ritual. Hasil penelitian menunjukkan bahwa ritual setelah kematian di Aceh masih mengandung jejak warisan pra-Islam yang telah dibiakkan dengan ajaran Islam sehingga tidak melangar aturan Islam. Dalam ritual kematian ini, unsur-unsur pra-Islam, yang bertentangan dengan ajaran Islam, telah diganti dengan doa yang direkomendasikan dalam Islam. Akulturasi ini bermanfaat bagi kedua belah pihak. Masyarakat Aceh dapat terus menerapkan budaya warisan mereka, sementara Islam dapat berkembang tanpa ada kontradiksi dalam budaya lokal.Abstract: This study was conducted to look into the cultural and religious acculturation in the rituals of death in Aceh. It aims to examine the concepts of Sufism related to these traditions. This research is a field research and its data was obtained through meticulous observation of the ritual action and in-depth discussion with the main protagonists of the ritual performance. The results of the research shows that the rituals following a death in Aceh still bear traces of their pre-Islamic legacy, which has been acculturated with the teachings of Islam, so it does not break the rules of Islam. In these rituals for death, the pre-Islamic elements, which conflict with the Islamic creed, have been replaced with prayers, which are recommended in Islam. This acculturation is beneficial to both sides, in one hand the Acehnese people may continue to implement their inherited cultures, while Islam can thrive without having any contradictions within the local cultures on the other. Keywords: tradisi, ritual yang mengikuti kematian, akulturasi, Aceh, Indonesia